Factors associated with depressive symptoms among returnee migrants and non-migrants working adults in Madi municipality in Nepal: a community-based cross-sectional study - Pratik Adhikary; Hridaya Raj Devkota; Arthur L. Reingold; Dirgha J. Ghimire (BMC, 2024)
Abstract Background Mental health is a growing concern worldwide. It is not well understood whether international labour migrants from Nepal who return to Nepal are at higher risk of developing mental health problems. The purpose of our study was to determine the prevalence of and examine the associated factors for depressive symptoms among returnee migrants and non-migrant working male adults in Nepal. Methods A cross-sectional survey of a probability-based sample of 725 participants was conducted in February 2020. The sample was comprised of two groups based on migration status: returning migrants and non-migrants. The 21-item Beck Depression Inventory (BDI-21) questionnaire was used to assess depressive symptoms. Logistic regression was applied to investigate factors associated with symptoms of depression. Results The overall prevalence of depressive symptoms was 10.1%. However, the prevalence of depressive symptoms was lower (7%) among returnee migrants compared to non-migrants (13.7%). Men in the lower income group had a higher chance of having depressive (AOR = 5.88, 95% CI: 2.17-15.96) than those in the higher income group. Similarly, Buddhists and Christians were more likely to be depressed (AOR = 2.20, 95% CI: 1.03-4.68) than Hindus. Participants with more than two children had a higher chance of having of depressive symptoms (AOR = 4.80, 95% CI: 1.15-20.05) compared with those without children. Unmarried men were more likely to be depressed (AOR = 4.07, 95%, CI:1.11-14.92) than those who were married. Conclusion The working Nepali adult male population in Nepal, including returning migrants, is at risk of depressive symptoms, but this association was lower in those in the higher income group, returnee migrants, those who were married, Hindus and those with no children. Our results highlight the need to monitor and develop national policies to ensure the mental health of the Nepali male adult population, including returnee migrants.